A Comparative Study on the Solutions of 4th Order Differential Equations With Boundary Conditions - Krishna, C. Balarama; Rao, S. Vishwa Prasad; Endla, Purushotham (Communications in Mathematics and Applications, 2022)
In the present study, we have investigated the differential equations of order four to evolve the methods to achieve the solution for differential equations. Absolute Stability Region (ASR) of the differential equations has been examined. Numerical Differentiation (ND) and Differential Transform Method (DTM) which are suggested and derived in this article are much suitable to understand the solutions of differential equations of fourth order. Both the methods are applied to some differential equations, numerical examples and results are presented to outline the capability and robustness of our strategies and compared them with that of exact solution.